2023
DOI: 10.1111/codi.16707
|View full text |Cite
|
Sign up to set email alerts
|

From diagnosis of colorectal cancer to diagnosis of Lynch syndrome: The RM Partners quality improvement project

Laura Monje‐Garcia,
Timothy Bill,
Lindsay Farthing
et al.

Abstract: AimThe UK National Institute for Health and Care Excellence guideline DG27 recommends universal testing for Lynch syndrome (LS) in all newly diagnosed colorectal cancer (CRC) patients. However, DG27 guideline implementation varies significantly by geography. This quality improvement project (QIP) was developed to measure variation and deliver an effective diagnostic pathway from diagnosis of CRC to diagnosis of LS within the RM Partners (RMP) West London cancer alliance.MethodRM Partners includes a population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This improvement will be related to several key advantages, such as its low cost, scalability, clarity of results, and delivery by technologists rather than senior scientists or pathologists, that address the previously identified barriers to LS screening [ 11 – 13 ]. However, it has also been shown that LS screening quality improvement programmes that focus on educating healthcare providers and connecting clinical services, rather than employing new technologies, significantly increase tumour testing [ 37 ]. Therefore, the improved testing observed here at the regional-level will also reflect the impact of the English National Lynch Syndrome transformation project, which has appointed over 200 local LS Champions across England and established a national forum and data service to monitor LS screening, among other advances [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This improvement will be related to several key advantages, such as its low cost, scalability, clarity of results, and delivery by technologists rather than senior scientists or pathologists, that address the previously identified barriers to LS screening [ 11 – 13 ]. However, it has also been shown that LS screening quality improvement programmes that focus on educating healthcare providers and connecting clinical services, rather than employing new technologies, significantly increase tumour testing [ 37 ]. Therefore, the improved testing observed here at the regional-level will also reflect the impact of the English National Lynch Syndrome transformation project, which has appointed over 200 local LS Champions across England and established a national forum and data service to monitor LS screening, among other advances [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These downstream barriers are also being targeted by the English National Lynch Syndrome transformation project [ 35 ], including updates to molecular reporting to ease clinical interpretation, education of multi-disciplinary teams on results interpretation and germline testing referral, and the mainstreaming of genetic testing. As shown for increased MMR deficiency testing rates, such programmes have increased referrals for germline analysis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients eligible for constitutional (germline) testing for LS who were identified and effectively referred increased from 10% to 74% across the life cycle of this QIP. 42 These data formed the basis for a successful bid to NHS England to fund a national transformational project.…”
Section: Pilot Projectmentioning
confidence: 99%